Infections Caused by Stenotrophomonas maltophilia in Recipients of Hematopoietic Stem Cell Transplantation - Al-Anazi, Khalid Ahmed; Al-Jasser, Asma M. (Frontiers in Oncology, 2014)
Stenotrophomonas maltophilia (S. maltophilia) is a globally emerging Gram-negative bacillus that is widely spread in environment and hospital equipment. Recently, the incidence of infections caused by this organism has increased, particularly in patients with hematological malignancy and in recipients of hematopoietic stem cell transplantation (HSCT) having neutropenia, mucositis, diarrhea, central venous catheters or graft versus host disease and receiving intensive cytotoxic chemotherapy, immunosuppressive therapy, or broad-spectrum antibiotics. The spectrum of infections in HSCT recipients includes pneumonia, urinary tract and surgical site infection, peritonitis, bacteremia, septic shock, and infection of indwelling medical devices. The organism exhibits intrinsic resistance to many classes of antibiotics including carbapenems, aminoglycosides, most of the third-generation cephalosporins, and other β-lactams. Despite the increasingly reported drug resistance, trimethoprim-sulfamethoxazole is still the drug of choice. However, the organism is still susceptible to ticarcillin-clavulanic acid, tigecycline, fluoroquinolones, polymyxin-B, and rifampicin. Genetic factors play a significant role not only in evolution of drug resistance but also in virulence of the organism. The outcome of patients having S. maltophilia infections can be improved by: using various combinations of novel therapeutic agents and aerosolized aminoglycosides or colistin, prompt administration of in vitro active antibiotics, removal of possible sources of infection such as infected indwelling intravascular catheters, and application of strict infection control measures.